Organic solar cell and preparation method thereof
By combining the organic electron acceptor material with the ZnO precursor solution in the sol-gel method to form a nanoparticle precursor solution, the problem of poor contact between the ZnO film and the organic material is solved, and the photoelectric conversion efficiency of the organic solar cell is significantly improved.
Patent Information
- Application Number
- CN202411812206.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-10
AI Technical Summary
In the prior art, zinc oxide (ZnO) films have difficulty in forming good contact with organic materials due to their inorganic properties, and have low charge mobility and many surface defects, which hinder the effective transmission of electrons.
By combining the hydrophobic organic electron acceptor material with the ZnO precursor solution in the sol-gel method, a nanoparticle precursor solution is formed and stored at a constant temperature at a preset temperature to obtain a cathode interface layer solution that can be dissolved in a polar solvent, thereby achieving organic doping modification of the ZnO film.
The photoelectric conversion efficiency of organic solar cells is significantly improved, the contact between the electron transport layer and the active layer is improved, the electron mobility of ZnO is enhanced, and its surface defects are reduced.
Smart Images

Figure CN119816175A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic solar cells, and in particular to an organic solar cell doped with ZnO using an organic electron acceptor and a preparation method thereof. Background Art
[0002] Zinc oxide (ZnO) is widely used as the cathode interface layer in flip-chip organic solar cells due to its excellent photoelectric properties, good solution processability and simple processing methods. Since ZnO is an inorganic material, it is difficult to form a good contact with the organic material of the active layer, and the low charge mobility and large number of surface defects of ZnO also hinder the transmission of electrons. Therefore, the doping modification of ZnO thin films with organic materials to improve device performance is a current research hotspot. However, most organic electron acceptor materials are hydrophobic materials and cannot be dissolved in the polar solvents used to prepare ZnO thin films by the sol-gel method. Summary of the invention
[0003] The purpose of the embodiments of the present invention is to provide a method for preparing an organic solar cell, so that a hydrophobic organic electron acceptor material can be dissolved in a polar solvent for preparing a ZnO thin film by a sol-gel method, thereby achieving organic doping modification of the cathode interface layer material ZnO thin film and significantly improving the device's photoelectric conversion efficiency.
[0004] The present invention provides a method for preparing an organic solar cell, the preparation method comprising:
[0005] Providing an ITO substrate, forming a cathode interface layer on the ITO substrate, and forming an active layer on the cathode interface layer;
[0006] forming an anode interface layer on the active layer, and forming an anode layer on the anode interface layer;
[0007] Wherein, forming a cathode interface layer on the ITO substrate comprises:
[0008] preparing a ZnO precursor solution and an organic electron acceptor solution;
[0009] Stirring the ZnO precursor solution at a first rotation speed, and during the stirring of the ZnO precursor solution, adding the organic electron acceptor solution dropwise into the ZnO precursor solution to form a ZnO nanoparticle precursor solution;
[0010] After completing the operation of adding the organic electron acceptor solution to the ZnO precursor solution, the ZnO nanoparticle precursor solution is heated to a preset temperature, and the ZnO nanoparticle precursor solution is kept at a constant temperature for a first period of time at the preset temperature to obtain a cathode interface layer solution; and the cathode interface layer solution is coated on the ITO substrate to form a cathode interface layer.
[0011] Furthermore, the organic electron acceptor can be PC 71 BM or PC 61 One of BM or IT4F.
[0012] Furthermore, the doping volume ratio of the precursor solution to the organic electron acceptor solution is 1:1.
[0013] Further, before the ZnO precursor solution is stirred at the first rotation speed, or during the stirring of the ZnO precursor solution at the first rotation speed, the ZnO precursor solution is heated so that the temperature of the ZnO precursor solution reaches a first temperature; and / or, before the organic electron acceptor solution is added dropwise to the ZnO precursor solution, the organic electron acceptor solution is heated so that the temperature of the organic electron acceptor solution reaches a second temperature. The first temperature is higher than room temperature and lower than the second temperature.
[0014] Furthermore, the first temperature is 35-50 degrees; the second temperature is 60-65 degrees, the first rotation speed is 1000-1500rpm, and the preset temperature is 60 degrees.
[0015] Furthermore, the active layer materials are PM6 and L8BO, and the mass ratio of PM6:L8BO is 1:1.2. And / or, the anode interface layer is MoO3 with a thickness of 10nm; the anode layer is Ag with a thickness of 100nm.
[0016] Furthermore, the preparation of the ZnO precursor solution includes: in air, using ethylene glycol monomethyl ether as a solvent and ethanolamine as an additive to prepare a solution with a concentration of 100 mg / ml of zinc acetate dihydrate; stirring for a first period of time to obtain the ZnO precursor solution, wherein the addition percentage of the ethanolamine is 2.8%.
[0017] Furthermore, the preparation of the organic electron acceptor solution includes: preparing the organic electron acceptor into a first solution with a concentration of 1 mg / ml using chloroform as a solvent; heating the first solution to a second temperature and stirring for a second time to obtain the organic electron acceptor solution.
[0018] Further, in forming the cathode interface layer on the ITO substrate, the method includes: providing a single ethylene glycol monomethyl ether solution as a first precursor solution, and preparing an organic electron acceptor solution;
[0019] Stirring the first precursor solution at a first rotation speed, and during the stirring of the first precursor solution, adding the organic electron acceptor solution dropwise into the first precursor solution to form a first nanoparticle precursor solution;
[0020] After completing the operation of adding the organic electron acceptor solution to the first precursor solution, heating the first nanoparticle precursor solution to a preset temperature, and keeping the first nanoparticle precursor solution at a constant temperature for a second time at the preset temperature, adding zinc acetate dihydrate and ethanolamine to the first nanoparticle precursor solution, and stirring for a third time to obtain a cathode interface layer solution; coating the cathode interface layer solution on the ITO substrate to form a cathode interface layer.
[0021] Furthermore, the above-mentioned preparation method is used to prepare an organic solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A schematic structural diagram of an organic solar cell 100 provided by the present invention;
[0023] Figure 2 A schematic diagram of a preparation process of an organic solar cell provided by an embodiment of the present invention;
[0024] Figure 3 The dynamic light scattering diagrams of different nanoparticles prepared in Examples 1-3 of the present invention;
[0025] Figure 4 The figure is a relationship diagram between current density and voltage of the solar devices of the comparative example and embodiments 1-3 under illumination conditions.
[0026] Reference numerals:
[0027] 1- cathode substrate; 2- cathode interface layer; 3- active layer; 4- anode interface layer; 5- anode layer. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.
[0030] It should also be understood that the terms used in this specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used in the specification of the present invention and the appended claims, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include plural forms.
[0031] It should be further understood that the term "and / or" used in the present description and the appended claims refers to any and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0032] In conjunction with the accompanying drawings, some embodiments of the present application are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0033] The present invention provides an organic solar cell and a preparation method thereof. By adopting nanoparticle technology, a hydrophobic organic electron acceptor is successfully doped into ZnO as a composite cathode interface layer to prepare an organic solar cell device, thereby improving the contact between the electron transport layer and the active layer and improving the photoelectric efficiency of the solar cell. Figure 1 The organic solar cell 100 shown includes a cathode substrate 1, a cathode interface layer 2, an active layer 3, an anode interface layer 4, and an anode layer 5. Exemplarily, the organic solar cell 100 is prepared by the preparation method described below.
[0034] Reference Figure 2 , Figure 2 The present invention is a flowchart of the steps corresponding to the method for preparing an organic solar cell.
[0035] like Figure 2 As shown, the preparation method includes steps S101 to S105.
[0036] Step S101: providing an ITO substrate.
[0037] Exemplarily, the cathode substrate 1 is an ITO substrate
[0038] The ITO cathode substrate was first ultrasonically cleaned with acetone for 10 minutes, then cleaned with deionized water and detergent for 5 minutes, and then cleaned with pure water for 5 minutes. The pure water cleaning was repeated three times, and then cleaned with isopropanol for 10 minutes. Finally, the glass was blown dry with a nitrogen gun and then irradiated with a UV-ozone machine for 15 minutes to obtain the required ITO substrate.
[0039] It is understandable that the cleaning time depends on the surface area of the cathode substrate. Any equivalent replacement or change of the cleaning agent or the cleaning sequence by those skilled in the art should be included in the protection scope of the present invention.
[0040] Step S102: forming a cathode interface layer on the ITO substrate, wherein the forming of the cathode interface layer on the ITO substrate comprises: preparing a ZnO precursor solution and an organic electron acceptor solution; stirring the ZnO precursor solution at a first rotation speed, and during the stirring of the ZnO precursor solution, adding the organic electron acceptor solution dropwise to the ZnO precursor solution to form a ZnO nanoparticle precursor solution, and after completing the operation of adding the organic electron acceptor solution to the ZnO precursor solution, heating the ZnO nanoparticle precursor solution to a preset temperature, and maintaining the ZnO nanoparticle precursor solution at a constant temperature for a first period of time at the preset temperature to obtain a cathode interface layer solution, and coating the cathode interface layer solution on the ITO substrate to form a cathode interface layer.
[0041] Exemplarily, the organic electron acceptor comprises PC 61 BM or PC 71 One of BM or IT4F.
[0042] Embodiment 1, the organic electron acceptor is PC 61 BM, cathode interface layer 2 is PC 61 BM: ZnO layer.
[0043] A ZnO precursor solution and an organic electron acceptor solution were prepared. In the air, zinc acetate dihydrate was prepared with ethylene glycol monomethyl ether as a solvent and ethanolamine as an additive to prepare a solution with a concentration of 100 mg / ml. The percentage of ethanolamine added was 2.8%. After magnetic stirring for 1 hour, a ZnO precursor solution was obtained. PC 61 BM was prepared into a 1 mg / ml solution with chloroform as solvent, and PC was obtained after magnetic stirring at 60 degrees for 1 hour. 61 BM solution; place the ZnO precursor solution on a heating stirrer at a temperature of 40 degrees and a rotation speed of 1500rpm, and use a 10ml small syringe to take the above PC in a volume ratio of 1:1 with the ZnO precursor solution 61 BM solution, and the above PC 61The BM solution was added dropwise to the ZnO precursor solution, and stirring was stopped after the addition was complete to obtain a ZnO nanoparticle precursor solution. The ZnO nanoparticle precursor solution was heated to 65 degrees and evaporated for 2 hours to obtain a cathode interface layer solution.
[0044] Finally, the cathode interface layer solution is spin-coated on the surface of the ITO cathode substrate 1 treated in step S101 to obtain the cathode interface layer 2, the spin-coating speed is 3000-4000 rpm, the spin-coating time is 30 s, and the cathode interface layer 2 is annealed at 200 degrees for 30 minutes after spin-coating.
[0045] It should be noted that during the addition process, the ZnO precursor solution should be kept at a temperature higher than room temperature but lower than the boiling point of chloroform (61.2 degrees). Exceeding this range will cause the particles to agglomerate quickly, so that the size of the obtained particles exceeds nanometers, which has a negative impact on the final efficiency of the device. The temperature of the organic electron acceptor solution needs to be close to the boiling point of chloroform and maintained at 60-65 degrees. Too low a temperature may accelerate the agglomeration of particles, and too high a temperature may cause the ethylene glycol methyl ether in the ZnO precursor solution to volatilize, affecting the final concentration of zinc oxide. At the same time, since the residual chloroform will also affect the crystallization and film formation of zinc oxide, after the addition is completed and the stirring is stopped, the temperature of the ZnO nanoparticle precursor solution needs to be increased to 60-65 degrees, so that the chloroform solvent of the organic electron acceptor solution evaporates to a liquid level that is almost the same as the liquid level of the ZnO precursor solution before the addition, and no agglomeration occurs, that is, the cathode interface layer solution is obtained.
[0046] It will be appreciated that the evaporation time of the chloroform solvent depends on the amount of the solvent used.
[0047] Embodiment 2, different from the first embodiment, in this embodiment, the organic electron acceptor is PC 71 BM, that is, the cathode interface layer 2 is PC 71 BM: ZnO layer.
[0048] Embodiment 3 is different from the first embodiment. In this embodiment, the organic electron acceptor is IT4F, that is, the cathode interface layer 2 is an IT4F:ZnO layer.
[0049] In some embodiments, such as Embodiment 4, a single ethylene glycol monomethyl ether solution is used as a precursor solution, and an organic electron acceptor solution is prepared, and PC 61 BM was prepared into a 1 mg / ml solution with chloroform as solvent, and PC was obtained after magnetic stirring at 60 degrees for 1 hour. 61 BM solution; place a single ethylene glycol monomethyl ether solution on a heating stirrer at a temperature of 40 degrees and a rotation speed of 1500rpm, and use a 10ml small syringe to take the above PC in a volume ratio of 1:1 with the ZnO precursor solution 61 BM solution, and the above PC 61The BM solution was added dropwise to the ethylene glycol monomethyl ether solution, and stirring was stopped after the addition was completed to obtain a nanoparticle precursor solution. The nanoparticle precursor solution was heated to 65 degrees and volatilized for 2 hours, and then zinc acetate dihydrate was added to make the concentration of zinc acetate dihydrate in the solution 100 mg / ml, and ethanolamine was added as an additive, and the addition percentage of ethanolamine was 2.8%, and the cathode interface layer solution was obtained by magnetic stirring for 1 hour.
[0050] Finally, the cathode interface layer solution is spin-coated on the surface of the ITO cathode substrate 1 treated in step S101 to obtain the cathode interface layer 2, the spin-coating speed is 3000-4000 rpm, the spin-coating time is 30 s, and the cathode interface layer 2 is annealed at 200 degrees for 30 minutes after spin-coating.
[0051] It should be noted that during the dropwise addition process, the precursor solution should be kept at a temperature higher than room temperature but lower than the boiling point of chloroform (61.2 degrees). Exceeding this range will cause the particles to agglomerate quickly, so that the size of the obtained particles exceeds the nanometer, which has a negative impact on the final efficiency of the device. The temperature of the organic electron acceptor solution needs to be close to the boiling point of chloroform, maintained at 60-65 degrees. Too low a temperature may accelerate the agglomeration of particles, and too high a temperature may cause the ethylene glycol methyl ether in the precursor solution to volatilize, affecting the final concentration of zinc oxide. At the same time, since the residual chloroform will also affect the crystallization and film formation of zinc oxide, after the dropwise addition is stopped and stirring is stopped, the temperature of the nanoparticle precursor solution needs to be increased to 60-65 degrees, so that the chloroform solvent of the organic electron acceptor solution evaporates to a liquid level that is almost the same as the liquid level of the precursor solution before the dropwise addition, and no agglomeration occurs. Then, zinc acetate dihydrate and ethanolamine are added, and the cathode interface layer solution is obtained by magnetic stirring for 1 hour.
[0052] It will be appreciated that the evaporation time of the chloroform solvent depends on the amount of the solvent used.
[0053] Step S103: forming an active layer on the cathode interface layer.
[0054] Exemplarily, the preparation process of the active layer 3 is as follows: in nitrogen, PM6 and L8BO are dissolved in chloroform, wherein the mass ratio of PM6:L8BO is 1:1.2, the PM6 concentration is 7.2 mg / ml, the additive is diiodomethane, and the added concentration of diiodomethane is 0.25%. After heating at 40 degrees and magnetically stirring for 30 minutes, an active layer solution is obtained. Finally, the active layer solution is spin-coated on the surface of the cathode interface layer 2 to obtain the active layer 3. The spin-coating speed is 3000 rpm, the spin-coating time is 30 seconds, and after spin-coating, annealing is performed at 100 degrees for 5 minutes.
[0055] Step S104: forming an anode interface layer on the active layer.
[0056] Exemplarily, MoO 3 is evaporated on the surface of the active layer 3 at a rate of 0.05 A / s as the anode interface layer 4 , and the thickness of the anode interface layer 4 is 10 nm.
[0057] Step S105: forming an anode layer on the anode interface layer.
[0058] Exemplarily, Ag is evaporated on the surface of the anode interface layer 4 at a rate of 0.2-1 A / s as the anode layer 5, and the thickness of the anode layer 5 is 100 nm.
[0059] Comparative Example
[0060] The preparation conditions of the comparative example are basically the same as those of Example 1, except that the cathode interface layer is ZnO and is not doped with other materials.
[0061] Figure 3 PC was prepared for Example 1-3 61 BM, PC 71 The dynamic light scattering patterns of BM and IT4F nanoparticles show that PC 61 BM and PC 71 The particle sizes of the nanoparticles of BM and IT4F are both around 100 nm, and the particle size of the nanoparticles of IT4F is between 300-400 nm, which proves that the present invention indeed disperses the organic electron acceptor material in the polar solvent of ZnO in the form of nanoparticles through the nanoparticle technology.
[0062] Figure 4 For the organic electron acceptor PC of Examples 1-3 61 BM, PC 71 The relationship curve between the current density and voltage of the organic solar cell with BM and IT4F doped with ZnO as the cathode modification layer and the organic solar cell with ZnO as the cathode modification layer in the comparative example under illumination conditions. It can be seen that the short-circuit current density (Jsc) of the organic solar cell with ZnO as the cathode modification layer in the comparative example is 23.07093mA / cm 2 , Example 1-3 Organic electron acceptor PC 61 BM, PC 71 The short-circuit current density (Jsc) of organic solar cells with BM and IT4F doped with ZnO as cathode modification layer is 23.90086 mA / cm 2 、24.80502mA / cm 2 and 25.50723mA / cm 2 This shows that the introduction of organic electron acceptors can effectively improve the charge transfer efficiency, thereby increasing the short-circuit current density.
[0063] Under standard test conditions: the photovoltaic characteristic parameters of Examples 1-3 and the comparative example are shown in Table 1. By comparison, it can be seen that the conversion efficiency of the comparative example is 14.49658% (Jsc is 23.07093 mA / cm 2 , Voc is 0.8889V, FF is 70.69175%). After the organic electron acceptor nanoparticles are incorporated, although the open circuit voltage decreases slightly, the short circuit current and the fill factor increase significantly, and the final efficiency is increased by 2.96% (Example 1), 12.11% (Example 2) and 15.53% (Example 3) compared with the original ZnO, respectively. This shows that the organic solar cell with the organic electron acceptor introduced into the ZnO cathode interface layer has its carrier mobility effectively improved.
[0064] Table 1 Photovoltaic characteristic parameters of Examples 1-3 and Comparative Examples
[0065] ETL <![CDATA[V oc (V)]]> <![CDATA[J SC (mA / cm 2 )]]> Fill Factor(%) Efficiency(%) Comparative Example ZnO 0.8889 23.07093 70.69175 14.49658 Example 1 <![CDATA[ZnO:PC 61 BM]]> 0.8769 23.90086 71.21797 14.92576 Example 2 <![CDATA[ZnO:PC 71 BM]]> 0.8731 24.80502 75.04319 16.25178 Example 3 ZnO:IT4F 0.8629 25.50723 76.09133 16.74786
[0066] Compared with the prior art, the present invention successfully converts PM into 61 BM, PC 71 Organic electron acceptor materials such as BM and IT4F are uniformly dispersed in the ZnO solution in the form of nanoparticles, so that n-type doping is formed in the electron transport layer. The organic electron acceptor materials work in coordination with the ZnO particles to form a composite inorganic-organic cathode interface layer, which regulates the energy level of the electron transport layer and improves the electron mobility of ZnO. The electron acceptor materials form good contact with the active layer materials at the interface. The doping of organic electron acceptor materials also passivates the ZnO layer and reduces its surface defects.
[0067] The above description is only a preferred specific implementation of the present invention, but the protection scope of the present invention is not limited thereto.
[0068] Any technician familiar with the technical field can make equivalent substitutions or changes according to the technical solution and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing an organic solar cell, characterized in that: include: Providing an ITO substrate, forming a cathode interface layer on the ITO substrate, and forming an active layer on the cathode interface layer; forming an anode interface layer on the active layer, and forming an anode layer on the anode interface layer; Wherein, forming a cathode interface layer on the ITO substrate comprises: preparing a ZnO precursor solution and an organic electron acceptor solution; Stirring the ZnO precursor solution at a first rotation speed, and during the stirring of the ZnO precursor solution, adding the organic electron acceptor solution dropwise into the ZnO precursor solution to form a ZnO nanoparticle precursor solution; After the organic electron acceptor solution is added to the ZnO precursor solution, the ZnO nanoparticle precursor solution is heated to a preset temperature, and the ZnO nanoparticle precursor solution is kept at a constant temperature for a first period of time at the preset temperature to obtain a cathode interface layer solution; The cathode interface layer solution is coated on the ITO substrate to form a cathode interface layer.
2. The preparation method according to claim 1, characterized in that: The organic electron acceptor is selected from PC 71 BM or PC 61 One of BM or IT4F.
3. The preparation method according to claim 1, characterized in that: The doping volume ratio of the precursor solution to the organic electron acceptor solution is 1:
1.
4. The preparation method according to claim 1, characterized in that: Before stirring the ZnO precursor solution at a first rotation speed, or during stirring the ZnO precursor solution at a first rotation speed, heating the ZnO precursor solution so that the temperature of the ZnO precursor solution reaches a first temperature; And / or, before adding the organic electron acceptor solution dropwise into the ZnO precursor solution, the organic electron acceptor solution is heated so that the temperature of the organic electron acceptor solution reaches a second temperature. The first temperature is higher than room temperature and lower than the second temperature.
5. The preparation method according to claim 4, characterized in that: The first temperature is 35-50 degrees; the second temperature is 60-65 degrees, the first rotation speed is 1000-1500rpm, and the preset temperature is 60 degrees.
6. The organic solar cell according to claim 1, characterized in that: The active layer materials are PM6 and L8BO, and the mass ratio of PM6:L8BO is 1:1.2; And / or, the anode interface layer is MoO3 with a thickness of 10 nm; the anode layer is Ag with a thickness of 100 nm.
7. The organic solar cell according to any one of claims 1 to 6, characterized in that: The method for preparing the ZnO precursor solution comprises: In air, zinc acetate dihydrate is prepared into a solution with a concentration of 100 mg / ml using ethylene glycol monomethyl ether as a solvent and ethanolamine as an additive; after stirring for a first period of time, the ZnO precursor solution is obtained, wherein the addition percentage of the ethanolamine is 2.8%.
8. The organic solar cell according to any one of claims 1 to 6, characterized in that: The method for preparing the organic electron acceptor solution comprises: The organic electron acceptor is prepared into a first solution with a concentration of 1 mg / ml using chloroform as solvent; The first solution is heated to a second temperature and stirred for a second period of time to obtain the organic electron acceptor solution.
9. The preparation method according to claim 1, characterized in that: The cathode interface layer is formed on the ITO substrate, comprising: Providing a single ethylene glycol monomethyl ether solution as a first precursor solution and preparing an organic electron acceptor solution; Stirring the first precursor solution at a first rotation speed, and during the stirring of the first precursor solution, adding the organic electron acceptor solution dropwise into the first precursor solution to form a first nanoparticle precursor solution; After the organic electron acceptor solution is added to the first precursor solution, the first nanoparticle precursor solution is heated to a preset temperature, and the first nanoparticle precursor solution is kept at a constant temperature for a second time at the preset temperature, zinc acetate dihydrate and ethanolamine are added to the first nanoparticle precursor solution, and stirred for a third time to obtain a cathode interface layer solution; The cathode interface layer solution is coated on the ITO substrate to form a cathode interface layer.
10. An organic solar cell, characterized in that: include: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
Organic solar cell taking Ti3C2Tx doped ZnO as cathode modification layer material and preparation method of organic solar cell
CN110931643A
Electron transport layer based on doped zno layer and method thereof
IN201911019219A